The influence of leadership style and motivation on the participation level of PMKRI Surabaya members - Imelda Mulia; Arif Hidayat (Jurnal Mantik, 2026)
Student organizations are important forums in the process of developing student capacity outside of formal academic activities. This study aims to analyze the influence of leadership style and motivation on the participation level of members of the Indonesian Catholic Student Association (PMKRI) Surabaya Branch for the 2024/2025 period. Member participation is an important indicator of the success of a student organization because it is related to the sustainability of work programs and organizational effectiveness. This study uses a quantitative approach with a causal associative research type. The study population was all 190 active members of PMKRI Surabaya Branch, with a sampling technique using simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the help of the SPSS program. The results showed that leadership style had a positive and significant effect on member participation. Motivation also had a positive and significant effect on member participation. Simultaneously, leadership style and motivation had a significant effect on member participation with a coefficient of determination of 55.6%, while the rest was influenced by other factors outside the study. The findings of this study indicate that effective leadership and high motivation can increase member involvement in organizational activities